THE USE OF ENGLISH ANIMATED MOVIE TO IMPROVE STUDENTSâ ABILITY IN WRITING DESCRIPTIVE TEXT - Wahyuni, Sri (STKIP Bina Bangsa Getsempena Banda Aceh, 2017)
The objective of this study was to investigate the effectiveness of using English animated movie in writing descriptive text and to figure out the students responds in using of English animated movie in their writing descriptive text to the fourth semester of English department at STKIP Bina Bangsa Getsempena. In this research, there were 12 students that took as a sample. The data was obtained through quantitative and qualitative design method. The quantitative data was taken from the studentsâ writing score, while qualitative data was obtained from the questionnaire which were distributed to figure out the students respond in using English animated movie in their writing descriptive text. The data collected by using two steps of test, there are pre-test and post-test. The post-test result was 83.5 and the mean of pre-test was 75.25. It meant that the post-test mean is higher than the pre-test, while the score of t-test was 22.88.Keyword: English Animated Movie, Descriptive Text, Writing Skill